Green entrepreneurship intention among high school students: a teachers’ view - Perez-Luyo, Ricardo; Quiñones Urquijo, Abel; Del-Aguila-Arcentales, Shyla; Alvarez-Risco, Aldo (Frontiers in Education, 2023)
There is a gap in the view of teachers about green entrepreneurship intention in high school students. The objective of the current article is to evaluate the factors that explain from private high schools in Peru the intention of green entrepreneurship in private high school students from the view of teachers in Peru. It was carried out by prospective, quantitative, and correlational research with a sample size of 163 teachers from fifth high schools. The research model was evaluated by partial least square structural equation modeling (PLS-SEM) which is a technique for multivariate analysis. Extracurricular support and country support showed an effect on entrepreneurial selfefficacy. Also, entrepreneurial self-efficacy had an effect on green entrepreneurship intention. Finally, self-efficacy was a mediator between extracurricular support, country support, and green entrepreneurial intention. These outcomes can be used by the Ministry of Health and high school planners to use the variables that show more effect and include strategies to increase the green entrepreneurial intention among school students as the creation of annual programs of practical training and entrepreneurship accelerators to develop skills among the students. Also, it can be relevant that the professors can receive specific training in green entrepreneurship because they can guide their students during the daily classes and extracurricular activities as well.